2016
DOI: 10.3390/biomedicines4040024
|View full text |Cite
|
Sign up to set email alerts
|

Glioma FMISO PET/MR Imaging Concurrent with Antiangiogenic Therapy: Molecular Imaging as a Clinical Tool in the Burgeoning Era of Personalized Medicine

Abstract: The purpose of this article is to provide a focused overview of the current use of positron emission tomography (PET) molecular imaging in the burgeoning era of personalized medicine in the treatment of patients with glioma. Specifically, we demonstrate the utility of PET imaging as a tool for personalized diagnosis and therapy by highlighting a case series of four patients with recurrent high grade glioma who underwent 18F-fluoromisonidazole (FMISO) PET/MR (magnetic resonance) imaging through the course of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Other PET radiopharmaceuticals that are under investigation to differentiate between progression from pseudoprogression or tumor recurrence include 18 F-fluoromisonidazole (FMISO) PET/MR [48], 4-borono-2-[(18)F]-fluoro-phenylalanine ( 18 F-FBPA) PET [49], [(18)F]-fluoromethyl-dimethyl-2-hydroxyethylammonium ( 18 F-fluoromethylcholine) PET [50], and 3′-deoxy-3′-(18)F-fluorothymidine (FLT) PET [51].…”
Section: Diagnostic Imaging Modalitiesmentioning
confidence: 99%
“…Other PET radiopharmaceuticals that are under investigation to differentiate between progression from pseudoprogression or tumor recurrence include 18 F-fluoromisonidazole (FMISO) PET/MR [48], 4-borono-2-[(18)F]-fluoro-phenylalanine ( 18 F-FBPA) PET [49], [(18)F]-fluoromethyl-dimethyl-2-hydroxyethylammonium ( 18 F-fluoromethylcholine) PET [50], and 3′-deoxy-3′-(18)F-fluorothymidine (FLT) PET [51].…”
Section: Diagnostic Imaging Modalitiesmentioning
confidence: 99%
“…Accordingly, several preclinical studies in animal tumors documented elevations in tumor oxygenation (16,(29)(30)(31), whereas others reported increased intratumoral hypoxia (32)(33)(34) after the first few days of treatment with bevacizumab. The results from clinical studies in glioblastoma and breast cancer patients receiving bevacizumab therapy are equally contradictory, with some studies describing improvements in tumor oxygenation based on [ 18 F]fluoromisonidazole (FMISO) PET (35,36) or histology (37,38), and others reporting increases in intratumoral hypoxia based on FMISO uptake and/or diffuse optical spectroscopic imaging (DOSI) (39,40) and dynamic susceptibility contrast MRI (DSC-MRI) (41). Given the ability of eMSOT to provide accurate oxygenation readings at high spatiotemporal resolution and increased imaging depths, we hypothesized that longitudinal eMSOT imaging would offer valuable insights into the dynamics and spatial distribution of breast tumor oxygenation along the course of bevacizumab therapy.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, [ 18 F]FMISO PET has been used for monitoring the effects of antiangiogenic therapy with bevacizumab in patients with recurrent malignant glioma [132,133]. It was shown that patients who had a response in both contrast-enhanced MRI and [ 18 F]FMISO PET had significantly longer survival than patients who responded on MRI only [133].…”
Section: Pet Imaging Of Tumor Hypoxiamentioning
confidence: 99%